A Look into Anthrax as a Biological Weapon, from the Past to Today - Babak Shiravand; Ibrahim Salmani; Mohammad Reza Shokouhi; Farokhlegha Servat; Negar Karami (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: Biological attack a phenomenon which has seriously started in the 20th- century and is expanding every day. Plague agent is one of factors listed as a biological weapon by the disarmament convention. Therefore, the risk of biological or bioterrorism applications is probable and serious. The purpose of this study was to update health professionals' information on plague and bioterrorism aspect of this disease. Methods: This article is a literature review written based on search on articles from library and internet resources (1990- 2016). Results: More than 2,000 species of bacteria have been identified in three main groups of bacillus (rod-shaped), cocci (round and oval), and spiral. But only about 100 of them are known as pathogens and Less than 10 species are used as biological agents for military application and one of them is plague agent. Yersinia pestis is a Gram negative, rod-shaped, anaerobic, member of the enterobacteriaceae family, and if be painted by Colors Wright, Giemsa or Leeson will be seen bipolar under a microscope. Conclusion: Nowadays, in spite of the progresses made in science and technology, human knowledge is relatively incapable to anticipate the time and place of biological attacks. Therefore, being prepared and ready for its unavoidable occurrence is necessary. So, regarding the importance and necessity of readiness, officials and experts have to make an effort and plan against these hazards.